A Case Series of Floppy Neonates: A Chain is No Stronger than its Weakest Link - E, Adarsh; Prasad, Srinivas Mahesh; A, Sagethya; HS, Surabhi (Archives of Clinical and Medical Case Reports, 2022)
Floppy infant syndrome (FIS) can be caused by a variety of disorders. FIS categorised into four main groups, namely, the central nervous system, the spinal motor neuron, peripheral nerves, neuromuscular junction and the muscles. Neonates might appear with a variety of signs depending on the cause of hypotonia. The perinatal asphyxia is the most common cause of central hypotonia in newborns. Other causes of central hypotonia include brain malformations, chromosomal abnormalities and inborn errors of metabolism like Non-ketotic hyperglycaemia (NKH). Infancy has a 13% prevalence of neuronal dysmigration disorder, which causes hypotonia. Peripheral causes (30%) include spinal muscular atrophy, myasthenia gravis, drug/toxin exposure, hereditary neuropathies, muscular dystrophies, congenital/metabolic myopathies, and congenital myotonic dystrophies. We'll take a look at how central and peripheral hypotonia manifest themselves in neonates in this case series. This study involves five neonates who required resuscitation after delivery and NICU care due to respiratory distress, necessitating examination and evaluation in order to diagnose these conditions during the neonatal period. Though uncommon, a high index of suspicion is necessary for diagnosis and can help with antenatal counselling.